CAPACITY BUILDING OF WOMEN LEADERS VIA MANAGEMENT PROGRAMS - Ilisko, Dzintra; Juhneviča, Karīna; Badjanova, Jelena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
Despite of women advancement in politics, business, and other spheres of life, women are largely absent from senior position and are marginalized in terms of power and resources. In Latvia women set up and lead vibrant and successful governmental and private organizations. The purpose of the article is to explore cultural roots of gendered inequality in leadership and economic power positions by the literature review and as reviled in interviews.  Interview data reveal the obstacles women need to overcome in their career advancement and their stories of success. Methodology: The study presents a qualitative study on women’s leadership as defined in legislation and recent research and is supported by the qualitative inquiry of life stories of seven women engaged in the education’s management programs. These women undertake leadership positions in their organizations. Conclusions: To conclude, the goal of equal participation for both male and female players in all significant spheres of life as declared in the international legislation and the United Nations, declarations will strengthen democracy and will promote its proper functioning. The authors assert that higher education through management study programs can also build women’s capacity for leadership by assertiveness training and encouraging independent and critical thinkers.